Market power and forward prices - Keith Ruddell; Tony Downward; Andy Philpott (Research Institute of Industrial Economics (IFN), 2017)
We construct a model of strategic behavior in sequential markets which exhibits a persistent forward price premium. On the spot market, producers wield market power while purchasers are price takers. Producers with forward commitments have less incentive to raise prices on the spot market. Purchasers are thus willing to pay a premium to producers for forward contracts. We argue that this type of forward premium is not susceptible to arbitrage by speculators on the forward market, since purchasers prefer forward contracts backed by producers.
Keywords: D43; G13; L12; L13; Q41; 330; Forward pricing; Electricity markets; Market power; Arbitrage